Dinamika Global Penelitian Tax Planning Analisis Bibliometrik Dan Systematic Literature Review - Rocky Rocky; Fitriana Fitriana; Rachmat Agus Santoso (Universitas Dharmawangsa, 2026)
This study examines the global dynamics of tax planning research through a Systematic Literature Review (SLR) and bibliometric approach. The research aims to identify publication trends, dominant themes, influential countries, and research gaps related to tax planning studies indexed in Scopus from 1954–2025. Data were analyzed using Biblioshiny to map scientific publication patterns, keyword co-occurrence, citation networks, and thematic developments. The findings indicate that tax planning research has increased significantly, particularly after 2010, driven by issues such as tax avoidance, digital taxation, BEPS, global tax governance, and global minimum tax policies. The United States, Canada, and China dominate scientific publications in this field. The study also reveals that profitability, leverage, corporate governance, and international tax regulations are the most frequently discussed determinants influencing tax planning practices. These findings provide a systematic and comprehensive understanding of the development of global tax planning research.